ChemInform Abstract: Sodium Sulfide: A Sustainable Solution for Unbalanced Redox Condensation Reaction Between o‐Nitroanilines and Alcohols Catalyzed by an Iron—Sulfur System. Issue 42 (October 2015) - Nguyen, Thanh Binh; Ermolenko, Ludmila; Al‐Mourabit, Ali
Abstract Hydrated sodium sulfide plays a dual role as a precursor for the formation of the Fe/S redox catalyst, and as an external and noncompetitive, multi‐electron reducing agent.